1995
DOI: 10.1042/bj3100615
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence of HSP-1, a major protein of stallion seminal plasma: effect of glycosylation on its heparin- and gelatin-binding capabilities

Abstract: We report the complete amino acid sequence of HSP-1, a major protein isolated from stallion seminal plasma or acid extracts of ejaculated spermatozoa. The protein consists of 121 amino acids organized in two types of homologous repeats arranged in the pattern AA'BB'. Each of the 13-15-residue A-type repeats contains two O-linked oligosaccharide chains. The B-type repeats span 44-47 amino acids each, are not glycosylated, and have the consensus pattern of the gelatin-binding fibronectin type-II module. This dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 27 publications
(27 reference statements)
5
68
0
Order By: Relevance
“…Two Nglycosylation sites are predicted from the amino acid sequence [27,28], and preliminary results have confirmed that both chymases B and C are glycosylated [51]. Differences in glycosylation have been shown to affect the heparin affinity of antithrombin III [52] and horse seminal protein-1 (HSP-1) [53]. Both of these proteins occur naturally in two distinct forms which differ in affinity for heparin: for antithrombin III, it is the lower affinity form which is more highly glycosylated [52], while for horse seminal protein-1, it is the higher affinity form which is more highly glycosylated [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two Nglycosylation sites are predicted from the amino acid sequence [27,28], and preliminary results have confirmed that both chymases B and C are glycosylated [51]. Differences in glycosylation have been shown to affect the heparin affinity of antithrombin III [52] and horse seminal protein-1 (HSP-1) [53]. Both of these proteins occur naturally in two distinct forms which differ in affinity for heparin: for antithrombin III, it is the lower affinity form which is more highly glycosylated [52], while for horse seminal protein-1, it is the higher affinity form which is more highly glycosylated [53].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in glycosylation have been shown to affect the heparin affinity of antithrombin III [52] and horse seminal protein-1 (HSP-1) [53]. Both of these proteins occur naturally in two distinct forms which differ in affinity for heparin: for antithrombin III, it is the lower affinity form which is more highly glycosylated [52], while for horse seminal protein-1, it is the higher affinity form which is more highly glycosylated [53]. However, for both of these examples, the different forms gave relatively sharp bands on SDS/PAGE, with a readily discernable difference in molecular mass between the two forms of antithrombin III.…”
Section: Discussionmentioning
confidence: 99%
“…In stallion, HSP-1 (72 kDa, pI 5.6) was proved positively correlated with fertility and HSP-2, HSP-3 and HSP-4 were negatively correlated with fertility (Calvete et al, 1995;Brandon et al, 1999). However, the correlation between the seminal plasma proteins and its semen characteristics has not been investigated in bulls.…”
Section: Introductionmentioning
confidence: 98%
“…During this collection the first ejaculate is discarded, usually it consists of fluid, which is whitish milky in color. Then second ejaculate is collected in the same manner which is then used for the molecular analysis (Calvete et al, 1995;Brandon et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…The HBPs of bull and stallion seminal plasma, termed PDC-109, BSP-A3, and BSP-30K, and HSP-1 and HSP-2, respectively, are polypeptides with 109-121 amino acid residues made up of one or more 13-15-residue O-glycosylated N-terminal repeats followed by two tandemly arranged domains each sharing the consensus sequence of fibronectin type-II modules (see [5] and references therein). The heparin-binding proteins of boar seminal plasma belong to another protein family, called spermadhesins [6], whose members are structurally unrelated to the bovine and equine HBPs.…”
Section: Introductionmentioning
confidence: 99%